Virtual health care for adult patients with intellectual and developmental disabilities: A scoping review. Issue 4 (October 2021) - Selick, Avra; Bobbette, Nicole; Lunsky, Yona; Hamdani, Yani; Rayner, Jennifer; Durbin, Janet
Abstract: Background: The COVID-19 pandemic led to an abrupt shift to virtual health care for many patients, including adults with intellectual and developmental disabilities (IDD). Approaches to virtual care that are successful for people without IDD may need to be adapted for adults with IDD. Objective: The aim of this scoping review was to examine what is known about virtual health care for adults with IDD and in particular, the impact of virtual delivery on access to care for this population. Methods: A comprehensive search was conducted of the academic and grey literature. A two-stage screening process was conducted by two independent reviewers and a structured data extraction template was populated for each included study. Findings were analyzed thematically using Access to Care Framework domains. Results: In total, 22 studies met inclusion criteria. The majority were published in the past three years and focused on specialized IDD services. A subset of 12 studies reported findings on access to care for adults with IDD. Participants generally reported high acceptability of virtual care, though some preferred face-to-face encounters. Initial results on effectiveness were positive, though limited by small sample sizes. Challenges included internet quality and technical skill or comfort. Conclusions: This review suggests that it is possible to deliver accessible, high quality virtual care for adults with IDD, however, relatively little research has been conducted on this topic. Due to COVID-19 there is currently a unique opportunity and urgency to learn when and for whom virtual care can be successful and how it can be supported.